Bioreactor media for treatment of slag leachate. (December 2022) - Hunter, James G.; Kang, Dong Hee
Abstract: Blast furnace slag (BFS) used in the road construction as base/subbase materials leads to leachate problems under poor drainage conditions. The BSF leachate is a source of high pH, sulfur, and dissolved solids which will be affected to surrounding ecosystem. A column experiment was performed to evaluate the treatment of BFS leachate by media commonly used in passive treatment systems. The treatment efficiency of column media was assessed for inorganic (gravel and limestone) and organic (peat and mushroom compost) with zero-valent iron (ZVI). Columns were dosed with experimentally generated BFS leachate and operated under residence times of 7 and 14 days. The column depths of 45 cm and 75 cm allowed for determination of the role of anoxic conditions in the transformation, precipitation, and adsorption of dissolved constituents. The organic treatments were more effective for reducing pH, TDS, sulfate, and total sulfur. Mushroom compost, with ZVI and a residence time of 14 days, was the most effective matrix for the removal of sulfate (67%), and total sulfur (72%). Peat treatments resulted in the lowest pH at 6.34; however, concentrations of Al, Fe, Mg, and Mn were elevated. Organic biofilters utilizing sulfate-reducing bacteria (SRB) and ZVI may prove to be useful for treating BFS leachate and other sources of sulfur and TDS pollution. Graphical abstract: Image 1 Highlights: Organic media (Peat or Mushroom compost) effectively reduce pH, TDS, and total sulfur. Mushroom compost with ZVI combination is more effective matrix for the removal of sulfate and total sulfur. Organic biofilters utilizing sulfate-reducing bacteria (SRB) and ZVI may prove to be useful for treating BFS leachate.